1977
DOI: 10.1139/v77-368
|View full text |Cite
|
Sign up to set email alerts
|

The effect of substituents on geminal proton–proton coupling constants. III

Abstract: RAJ CAPOOR. Can. J. Chem. 55,2642Chem. 55, (1977.The effect of substituents at the 3-position in a series of N-methyl 5,6-dihydro-7H,l2H-dibenzo [c,f]azocines on the geminal coupling constants of the C-12 methylene protons has been determined. The slope of the Hammett plot of 'J us. o has been found to be + 0.20. The orientation of the methylene protons with respect to the n orbitals of the benzene ring bearing the substituent is such that no hyperconjugative effect should be present. The value of +0.20 is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1977
1977
2008
2008

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…The observed difference between these two J gem -couplings (24.0 − 20.7 = 3.3 Hz for ϕ = 0° and 23°, respectively) is consistent with the differences reported in ref (e.g., 23.6 − 18.1 = 5.5 Hz for ϕ = 0° and 45°, respectively)…”
Section: Referencessupporting
confidence: 91%
See 3 more Smart Citations
“…The observed difference between these two J gem -couplings (24.0 − 20.7 = 3.3 Hz for ϕ = 0° and 23°, respectively) is consistent with the differences reported in ref (e.g., 23.6 − 18.1 = 5.5 Hz for ϕ = 0° and 45°, respectively)…”
Section: Referencessupporting
confidence: 91%
“…In the case of the calculated planar structure of 1-syn, this dihedral angle is exactly 0°, thus this coupling reaches its maximum value. 14 In the case of 2, the bent geometry of the central ring causes the dihedral angle φ to become about 23°(according to DFT calculations), thus reducing the value of the J-coupling, as experimentally observed (i.e., -20.7 and -24.0 Hz in 2 and 1, respectively). 15 (ii) In the case of 2, the low-field hydrogen signal of the ABsystem displays a small additional 4 J coupling (0.95 Hz) with the two hydrogens in positions 4 and 5 of the anthrone ring, whereas the high-field hydrogen signal does not display such a coupling (Figure S-1 of the Supporting Information).…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…Recently we have shown that the hyperconjugative effect of a phenyl substituent on the geminal coupling constant of an attached methylene group varies from 0-5.5 Hz (19). Specifically the coupling coilstant is 5.5 Hz more negative when the rt orbitals of the ring and a line drawn through the two protons are parallel (projected angle + = 0") rather than perpendicular (+ = 90").…”
Section: -Methylmentioning
confidence: 99%